Cancer Immunotherapy: Historical Perspective of a Clinical Revolution and Emerging Preclinical Animal Models - Decker, William K.; da Silva, Rodrigo F.; Sanabria, Mayra H.; Angelo, Laura S.; Guimarães, Fernando; Burt, Bryan M.; Kheradmand, Farrah; Paust, Silke (Frontiers in Immunology, 2017)
At the turn of the last century, the emerging field of medical oncology chose a cytotoxic ap-proach to cancer therapy over an immune-centered approach at a time when evidence in support of either paradigm did not yet exist. Today, nearly 120 years of data have established that a) even the best cytotoxic regimens only infrequently cure late-stage malignancy and b) strategies, which supplement and augment existing antitumor immune responses offer the greatest opportunities to potentiate durable remission in cancer. Despite widespread acceptance of these paradigms today, the ability of the immune system to recognize and fight cancer was a highly controversial topic for much of the 20th century. Why this modern paradigmatic mainstay should have been both du-bious and controversial for such an extended period is a topic of considerable interest that merits candid discussion. Herein we review the literature to identify and describe the watershed events that ultimately led to the acceptance of immunotherapy as a viable regimen for the treatment of neoplastic malignancy. In addition to noting important clinical discoveries, we also focus on research milestones and the development of critical model systems in rodents and dogs including the advanced modeling techniques that allowed development of patient-derived xenografts. Together, their use will further our understanding of cancer biology and anti-tumor immunology, allow for a speedier assessment of the efficacy and safety of novel approaches, and ultimately provide a faster bench to beside transition.